Use of Phenobarbital to Treat Neonatal Abstinence Syndrome From Exposure to Single vs. Multiple Substances - Kushnir, Alla; Garretson, Cynthia; Mariappan, Maheswari; Stahl, Gary (Frontiers in Pediatrics, 2022)
Drug use in pregnancy is a major public health issue. Intrauterine exposure to opioids alone or in addition to other substances may lead to neonatal abstinence syndrome (NAS). Little consensus exists on optimal therapy, especially for those exposed to multiple drugs. We aim to determine whether the use of opioids alone vs. in combination with phenobarbital will affect short-term neonatal outcomes. This retrospective review of infants admitted to the neonatal intensive care unit (NICU) included newborns ≥35 weeks of gestation exposed to opioids, or multiple substances including opioids, in utero. Treatment with opioids alone, and addition of phenobarbital as initial therapy vs. rescue, was evaluated. Out of 182 newborns, 54 (30%) were exposed to methadone alone vs. 128 (70%) to multiple drugs. Length of stay (LOS) in the hospital was not significantly affected (p = 0.684) by single vs. multiple drug exposure in utero. Treatment of NAS with opioid alone resulted in significantly shorter LOS (27 days), as compared to those treated with opioid and phenobarbital (45 days, p < 0.001). LOS was further prolonged in those treated with phenobarbital as a “rescue” medication in addition to an opioid (49 days, p < 0.0001). There was a significant increase in LOS and duration of opioid treatment for all infants treated with phenobarbital, both in those exposed to opioids alone, and to multiple substances in utero.